Women trauma and stereotype tradition in Tunde Kelani’s film, thunderbolt (2018)
Stereotype tradition and gender injustice constitute the trauma that majority of women face in the marital relationship in Yoruba cultural setting. These issues was explore in Tunde Kelani’s film, Thunderbolt (Magun). Employing the narrative content analysis technique the film reveals various issues relating to women trauma in Yoruba stereotype tradition which empowers men against women. Suspicion, cultural chauvinism, betrayal, ambition, poor communication, lack of trust, wrong accusation and dominance constitute conflicts between couples in the film. This shows that the issue of conflict and gender injustice against women is a common traits in Yoruba cultural setting. The film is a lesson on many unresolved conflicts in marriages relationships while proposing trust and open communication which will improve and contribute to positive conjugal relationship development.